Isu Kepemimpinan Orang Bukan Islam Dalam Kerajaan Menurut Perspektif Fiqh - Mohd. Hapiz Mahaiyadin; Roshaimizam Suhaimi; Irwan Mohd Subri (Universiti Sains Islam Malaysia, 2024)
Non-Indexed Publication